Construction of VSVΔ51M oncolytic virus expressing human interleukin-12 - Abdulal, Rwaa H.; Malki, Jana S.; Ghazal, Ezdehar; Alsaieedi, Ahdab A.; Almahboub, Sarah A.; Khan, Muhammad Yasir; Alsulaiman, Reem M.; Ghaith, Mazen M.; Abujamel, Turki S.; Ganash, Magdah; Mahmoud, Ahmad Bakur; Alkayyal, Almohanad A.; et al. (Frontiers in Molecular Biosciences, 2023)
The use of oncolytic viruses (OVs) in combination with cytokines, such as IL-12, is a promising approach for cancer treatment that addresses the limitations of current standard treatments and traditional cancer immunotherapies. IL-12, a proinflammatory cytokine, triggers intracellular signaling pathways that lead to increased apoptosis of tumor cells and enhanced antitumor activity of immune cells via IFN-γ induction, making this cytokine a promising candidate for cancer therapy. Targeted expression of IL-12 within tumors has been shown to play a crucial role in tumor eradication. The recent development of oncolytic viruses enables targeted delivery and expression of IL-12 at the tumor site, thereby addressing the systemic toxicities associated with traditional cancer therapy. In this study, we constructed an oncolytic virus, VSVΔ51M, based on the commercially available VSV wild-type backbone and further modified it to express human IL-12. Our preclinical data confirmed the safety and limited toxicity of the modified virus, VSV-Δ51M-hIL-12, supporting its potential use for clinical development.